The Living Mirror and Learned Ignorance (Vivum Speculum et Docta Ignorantia) - Romanenko, Yuri (Stasis, 2015)
This article is devoted to an analysis of two essential concepts in Vladimir Bibikhin’s philosophy, the “living mirror” and “learned ignorance.” These concepts are presented in all of his major works, and have vital ontological, anthropological and epistemological importance in his oeuvre.